Aliskiren: Direct Renin Inhibitor Baru Pada Terapi Hipertensi - N. P. U. S. DEWI; I. G. A. A. E. AMANDARI; M. W.KRISNAYANTI; M. A. SARASMITA (HANG TUAH MEDICAL JOURNAL, 2018)
Abstract Hypertension is a condition when blood pressure increases chronically. Referring to the results of Riset Kesehatan Dasar (Riskesdas), Bali has a proportion of hypertension of 19.9%. Several epidemiological studies suggest that the risk of damage to various vital organs directly correlates with an increase in blood pressure. Therefore, it takes regularity in controlling and also taking antihypertensive drugs. The most common antihypertensive drugs currently used are angiotensin converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARBs). However, previous findings suggest that ACEI and ARB have not been fully effective in lowering blood pressure. To overcome these weaknesses, found a new direct renin inhibitor that is aliskiren. Aliskiren can block the renin-angiotensin-aldosterone system (RAAS) at the highest level, so the ability of aliskiren in lowering blood pressure can not be doubted. Aliskiren able to inhibit the conversion of angiotensinogen to angiotensin I, so it can lower blood pressure in a sustainable manner.